2010
DOI: 10.1016/j.jpba.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of genistein and its four phase II metabolites in blood by a sensitive and robust UPLC–MS/MS method: Application to an oral bioavailability study of genistein in mice

Abstract: The purpose of this research was to develop a sensitive and reproducible UPLC-MS/MS method to simultaneously quantify genistein, genistein-7-O-glucuronide (G-7-G), genistein-4’-O-glucuronide (G-4’-G), genistein-4’-O-sulfate (G-4’-S) and genistein-7-Osulfate (G-7-S) in mouse blood samples. After the method was fully validated over a wide linear range, it was applied to quantify the levels of genistein and its metabolites in a mouse bioavailability study. The linear response range were 19.5–10,000 nM for geniste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 31 publications
3
64
0
Order By: Relevance
“…In this case, the previously validated method by Supko in mouse plasma is comparable to the here-developed method [26]. However, no data regarding HPLC-UV validation methods in mouse tissues have been found, being the present study only comparable to already published HPLC GEN quantification methods coupled to a MS detector [23,31]. In these cases, LLOQ values of 0.1 ng/mL [19] and 1 ng/mL [21] in human serum, 8.5 ng/mL in human plasma [20] were reached.…”
Section: Linearity and Lloqmentioning
confidence: 51%
See 2 more Smart Citations
“…In this case, the previously validated method by Supko in mouse plasma is comparable to the here-developed method [26]. However, no data regarding HPLC-UV validation methods in mouse tissues have been found, being the present study only comparable to already published HPLC GEN quantification methods coupled to a MS detector [23,31]. In these cases, LLOQ values of 0.1 ng/mL [19] and 1 ng/mL [21] in human serum, 8.5 ng/mL in human plasma [20] were reached.…”
Section: Linearity and Lloqmentioning
confidence: 51%
“…The analyte was considered stable in the extracts of each biological matrix if 85-115% of the reference concentration was obtained. No further stability experiments were performed because the conditions had already been tested in human serum [21] and mouse plasma [26,31].…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A previous rodent study has indicate that more than 80% of genistein is converted to glucuronides and sulfates after both intravenous and oral administrations at 20 mg/ kg and that the absolute bioavailability is 23.4% [135]. Pharmacokinetic studies have shown that genistein has very long half-life (46 h) after oral administration and that different dose of genistein show no correlation of AUC, suggesting that there may be unknown mechanism of elimination and recycling system [135,136]. In human, genistein is extensively metabolized and the plasma level of unconjugated form is very low [137,138].…”
Section: Bioavailability Safety Tolerability and Pharmacokineticsmentioning
confidence: 99%
“…In this study the bioavailability at these three doses (estimated from AUCs after oral and after intravenous dosing) was 21.9 %, 33.5 % and 19.0%, respectively. Mice Yang et al (2010) investigated the systemic availability after i.v. and oral dosing of 20 mg/kg genistein in FVB mice.…”
Section: Genistein Monkeymentioning
confidence: 99%